Feeling shy - Althea (Milwaukee, WI : Gareth Stevens Pub., 1998)
Examines the nature of shyness, what can cause it, and how to deal with it.
Includes bibliographical references (p. 30) and index.
Accelerated Reader AR
Keywords: Bashfulness in children -- Juvenile literature; Bashfulness